Advancing Science Learning Outcomes with Quiver AR and Problem Based Learning - Andhini, Nadiya Solastika; Yamtinah, Sri; Daryanto, Joko (Universitas Sebelas Maret, 2026)
The rapid development of educational technology highlights the need for innovative learning approaches that can enhance students learning outcomes and support sustainable education in elementary schools. This study aims to examine how the integration of Quiver Augmented Reality (AR) and Problem Based Learning (PBL) contributes to improving learning outcomes and higher-order thinking skills in elementary education. This research employed a Systematic Literature Review (SLR) method by analyzing peer-reviewed journal articles published between 2021 until 2025 obtained from databases such as Scopus, Spinger Nature, ScienceDirect, Google Scholar, etc. The selected studies were reviewed using predefined inclusion and exclusion criteria and synthesized to identify research trends, instructional impacts, and implementation challenges. The findings indicate that the integration of Quiver AR and PBL consistently enhances students’ learning outcomes, particularly in science subjects, by improving conceptual understanding, learning engagement, and motivation. Additionally, most studies report positive effects on students critical thinking and problem solving skills due to the interactive and student centered nature of AR supported PBL environments. However, several challenges were identified, including limited teacher readiness, technical constraints, and the need for appropriate instructional design. Quiver AR integrated with Problem-Based Learning represents a promising educational technology innovation that supports effective, engaging, and sustainable learning in elementary education.